THE EFFECT OF DOSES Plant Growth Promoting Rhizobacteria (PGPR) Mimosa pudica ROOT ON GROWTH AND YIELD Asytasia gangetica IN DIFFERENT SOIL TYPES - G., Sembiring; Duarsa, M.A.P.; Roni, N.G.K. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This study aimed to determine the effect of gave doses Plant Growth Promoting Rhizobacteria (PGPR) Mimosa pudica root in different soil types on grownt dan yield Asystasia gangetica. This study used a completely randomized design (CRD) split plot pattern with two factors. The first factor is the types of soil as a main plot consisting of regosol soil (TR), latosol soil (TL), and mediteran soil (TM). The second factor is the doses of PGPR as a subplot/subplot which consisted of a dose 0 ml (P1), a dose 10 ml (P2), and a dose 20 ml (P3). There were nine treatment combination and each treatment was repeated four times so there were 36 experimental unit. The variable observed were growth variables, yield variables, dan plat growth characteristics variables. The resulTL showed that the first flowering variable had an interaction. The combination of TMP1 and TLP2 produced the highest value of 55 days at the first flowering. For the growth and yield of Asystasia gangetica, the use of regosol soil (TR) gave the best result, while the PGPR dose 10 ml (P2) gave the best resulTL. Concluded that the use of this regosol soil with a dose 10 ml of PGPR can increase the growth of Asystasia gangetica planTL.